Examination paediatrics - Harris, Wayne (Churchill Livingstone, 2011)
A practical study guide to help candidates pass clinical examinations in paediatrics, particularly at postgraduate level. Examination Paediatrics, 4th Edition is written for candidates preparing for the Fellowship Examination of the Royal Australasian College of Physicians (FRACP). This includes both Australian and New Zealand candidates as well as candidates taking the Australian examination in other countries.This invaluable paediatric study guide is also aimed at candidates preparing for the Membership Examination for the Royal College of Paediatrics and Child Health (UK) (Part II) (MRCPCH). Additionally, Examination Paediatrics will be a useful medical reference for all undergraduate and postgraduate students preparing for any paediatric exam with a clinical component - including those with an OSCE format. The new sections and expanded text in this fourth edition will assist General Practitioners, paediatric residents, house officers, registrars and doctors sitting the Australian Medical Council examination. Examination Paediatrics, 4th Edition contains ample information on history-taking, examination procedure, relevant investigations, memory aids, lists and mnemonics, and management for the majority of chronic paediatric clinical problems seen in hospital-based practice. This new edition retains a key feature popular in previous editions of Examination Paediatrics - a detailed explanation of the attitudinal skills, body language, and motivation necessary to complete clinical examinations successfully